2013
DOI: 10.1161/atvbaha.112.300388
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dietary Intake of Vitamin A Promotes Aortic Valve Calcification In Vivo

Abstract: Objective Calcific aortic valve disease (CAVD) is a major public health problem with no effective treatment available other than surgery. We previously showed that mature heart valves calcify in response to retinoic acid (RA) treatment through downregulation of the SRY-transcription factor Sox9. In this study, we investigated the effects of excess vitamin A and its metabolite RA on heart valve structure and function in vivo, and examined the molecular mechanisms of RA signaling during the calcification process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…RNA was extracted from murine VECs and pAVECs with Trizol according the manufactures protocol (Invitrogen) and cDNA and PCR reactions were performed as previously reported by our lab(31). Quantitative real-time PCR using a Step One Plus Real Time PCR system (Applied Biosystems) was used to detect changes in gene expression for Col4a2 , Itga1 , Rbm47 , Chrdl1 , Trim55 , and Hrh2 using Primetime assays from Integrated DNA Technologies; normalized to GAPDH and for α-SMA , Snai1, von Willebrand Factor (vWF) , and Tie2 using Taqman probes; normalized to 18S.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted from murine VECs and pAVECs with Trizol according the manufactures protocol (Invitrogen) and cDNA and PCR reactions were performed as previously reported by our lab(31). Quantitative real-time PCR using a Step One Plus Real Time PCR system (Applied Biosystems) was used to detect changes in gene expression for Col4a2 , Itga1 , Rbm47 , Chrdl1 , Trim55 , and Hrh2 using Primetime assays from Integrated DNA Technologies; normalized to GAPDH and for α-SMA , Snai1, von Willebrand Factor (vWF) , and Tie2 using Taqman probes; normalized to 18S.…”
Section: Methodsmentioning
confidence: 99%
“…Mitral and tricuspid valves were dissected from hearts of Scx +/− , and Scx +/+ ( wild type) mice at postnatal day 1 and cultured as explants on pore filters as previously described [21]. At the time of culture, BSA or 200 pM Tgfβ2 was added to the growth media [22] and explants were cultured for a further 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is still unclear whether dietary factors are significant independent risk factors for developing CAC. It is plausible that dietary factors increase risk of developing CAC since previous findings have shown that CAC is related to intake of phosphorous, vitamin A and vitamin D [9,10,11]. Nevertheless, there is little information supporting the relationships between CAC and macronutrients, such as carbohydrate, protein and fat intake.…”
Section: Introductionmentioning
confidence: 99%